Bark Beetle Attack History Does Not Influence the Induction of Terpene and Phenolic Defenses in Mature Norway Spruce (Picea abies) Trees by the Bark Beetle-Associated Fungus Endoconidiophora polonica - Nagel, Raimund; Hammerbacher, Almuth; Kunert, Grit; Phillips, Michael A.; Gershenzon, Jonathan; Schmidt, Axel (Frontiers in Plant Science, 2022)
Terpenes and phenolics are important constitutive and inducible conifer defenses against bark beetles and their associated fungi. In this study, the inducible defenses of mature Norway spruce (Picea abies) trees with different histories of attack by the spruce bark beetle, Ips typographus were tested by inoculation with the I. typographus-associated fungus Endoconidiophora polonica. We compared trees that had been under previous attack with those under current attack and those that had no record of attack. After fungal inoculation, the concentrations of mono-, sesqui-, and diterpenes in bark increased 3- to 9-fold. For the phenolics, the flavan-3-ols, catechin and gallocatechin, increased significantly by 2- and 5-fold, respectively, while other flavonoids and stilbenes did not. The magnitudes of these inductions were not influenced by prior bark beetle attack history for all the major compounds and compound classes measured. Before fungal inoculation, the total amounts of monoterpenes, diterpenes and phenolics (constitutive defenses) were greater in trees that had been previously attacked compared to those under current attack, possibly a result of previous induction. The transcript levels of many genes involved in terpene formation (isoprenyl diphosphate synthases and terpene synthases) and phenolic formation (chalcone synthases) were significantly enhanced by fungal inoculation suggesting de novo biosynthesis. Similar inductions were found for the enzymatic activity of isoprenyl diphosphate synthases and the concentration of their prenyl diphosphate products after fungal inoculation. Quantification of defense hormones revealed a significant induction of the jasmonate pathway, but not the salicylic acid pathway after fungal inoculation. Our data highlight the coordinated induction of terpenes and phenolics in spruce upon infection by E. polonica, a fungal associate of the bark beetle I. typographus, but provide no evidence for the priming of these defense responses by prior beetle attack.